A multiplex pharmacogenetics assay using the MinION nanopore sequencing device. Issue 9 (November 2019) - Liau, Yusmiati; Cree, Simone L.; Maggo, Simran; Miller, Allison L.; Pearson, John F.; Gladding, Patrick A.; Kennedy, Martin A.
Abstract : Objectives: The MinION nanopore sequencing device opens the opportunity to cost-effective and point-of-care DNA sequencing. As a proof of principle, we developed a multiplex assay targeting pharmacogenetic variants related to clopidogrel and warfarin, the two commonly used drugs that show response variability due to genetic polymorphisms. Methods: Six reference and 78 clinical DNA samples were amplified by PCR to generate 15 amplicons targeting 27 key variants. These products were then barcoded to enable sample multiplexing in one sequencing run. Four variant calling tools (marginCaller, VarScan 2, nanopolish, Clairvoyante) were used to compare genotyping accuracy. Results: In our cohort, 81 out of 84 samples were successfully sequenced and genotyped. Using nanopolish as the variant calling tool achieved accuracy >95% for all except two variants. A known single base deletion (CYP2C9*6) was successfully detected. Conclusion: While minor misgenotyping issues exist, this work demonstrates that drug-specific or broad pharmacogenetic screening assays using small PCR amplicons are possible on the MinION sequencing device. Abstract : Supplemental Digital Content is available in the text.